SWOT Matrix as a tool for diagnosing the municipal water supply system of a small city: a case study - Bona, Nicole Schweinberger; Silva, Silvana da; Hofer, Elza; Ramos, José Gustavo Venâncio da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
Small municipalities often face challenges related to their water supply systems, such as limited financial resources, low population densities and limited organizational capacity. In this context, this study aimed to diagnose the water supply system in the city of Quatro Pontes - PR, which serves 2,628 economies, through SWOT analysis. This analysis consisted of determining the strengths, weaknesses, opportunities and threats of the system, listed based on reports from employees and visual inspections. It was found that the system presents factors already documented for small municipalities with autonomous services, such as the strengths “good water quality” and “easy maintenance”, as well as the weaknesses “few financial resources applied” and “outdated pricing policy”. In addition, opportunities were mentioned, such as technological innovations in the sector, and threats related to water waste and contamination by pesticides. The results presented depict the water supply system of the municipality and can direct managers to take advantage of opportunities and mitigate system threats.